Women in Prison in the 1990s: A Temporal and Institutional Comparison - Kruttschnitt, Candace ([Verlag nicht ermittelbar], 2011)
This study explores the attitudes, perceptions and experiences of women in two prisons in California. The study includes both a temporal component comparing women's experiences in one prison in the early 1960s and the mid-1990s, and a comparative institutional component, comparing women's experiences in two different prisons operating in the social and policy milieu of the mid-1990s. It analyzes surveys of inmates and secondary data collected from official records, archives, and an earlier study of women in prison in California. The study portrayed women's reactions to prison as a function of (1) inmates' pre-prison characteristics, (2) characteristics of inmates' prison careers, (3) institutional structures and processes, (4) crime control ideologies and policies, (5) public attitudes toward crime and criminals, and (6) women's roles, opportunities, and lifestyles in the wider society. Closed-ended questions were developed for the survey designed to measure (1) the most difficult aspects of doing time, (2) the specific problems of prison life, (3) the various types of inmates and inmate relations, and (4) the nature of inmate-staff relations. The survey also included questions based on measures and scales used in penology research and the survey initially administered by Ward and Kassebaum to women prisoners in the 1960s. Demographic questions included age, ethnicity, if born in the United States, length of residence in the United States, marital status, and education.